2016
DOI: 10.1177/2455133316648052
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Freedom Influence Major Health Indicators in India? Cross-state Panel Estimation Results

Abstract: It is widely acknowledged that inadequacies in public sector health systems can only be overcome by substantial structural and institutional reforms. In India, the need for reforms in the health sector has been highlighted and stressed upon in recent period. While there is a growing belief that public and private sectors in health can potentially gain from one another, there is also recognition that, given their respective strengths and weaknesses, neither the public sector nor the private sector alone can ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…These findings are consistent in both the specifications (fixed effects and 2SLS) and confirm the results of previous studies (e.g. Esposto and Zaleski, 1999;Razvi and Chakraborty, 2016;Stroup, 2007). These results imply that sub-Saharan African countries should focus on improving the quality of economic institutions, which may include policies to strengthen the legal system, establish a system of property rights, reduce trade barriers and ease the regulatory burden.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent in both the specifications (fixed effects and 2SLS) and confirm the results of previous studies (e.g. Esposto and Zaleski, 1999;Razvi and Chakraborty, 2016;Stroup, 2007). These results imply that sub-Saharan African countries should focus on improving the quality of economic institutions, which may include policies to strengthen the legal system, establish a system of property rights, reduce trade barriers and ease the regulatory burden.…”
Section: Discussionsupporting
confidence: 90%
“…Esposto and Zaleski, 1999) and panel regression (e.g. Razvi and Chakraborty, 2016). One reason for this is that valid instruments are difficult to find, as shown by Feldmann (2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that women having bank accounts and mobile phones have made significant ANC visits compared to women with no bank account or mobile phone. Razvi and Chakraborty (2016) have found that economic empowerment significantly enhances healthcare utilisation by households. Most of the explanatory variables significantly affect the rate of ANC utilisation except the place of residence, religion and caste hierarchy.…”
Section: Resultsmentioning
confidence: 99%